E4F and ATF, two transcription factors that recognize the same site, can be distinguished both physically and functionally: a role for E4F in E1A trans activation. - Rooney, R J (1990)
Previous experiments have identified an element in the adenovirus E4 promoter that is critical for E1A-dependent trans activation and that can confer inducibility to a heterologous promoter. This DNA element is a recognition site for multiple nuclear factors, including ATF, which is likely a family of DNA-binding factors with similar DNA recognition properties. However, ATF activity was found not to be altered in any demonstrable way as a result of adenovirus infection. In contrast, another factor that recognizes this element, termed E4F, was found at only very low levels in uninfected cells but was increased markedly upon adenovirus infection, as measured in DNA-binding assays. Although both the ATF activity and the E4F activity recognized and bound to the same two sites in the E4 promoter, they differed in their sequence recognition of these sites. Furthermore, E4F bound only to a small subset of the ATF recognition sites; for instance, E4F did not recognize the ATF sites in the E2 or E3 promoters. Various E4F and ATF binding sites were inserted into an expression vector and tested by cotransfection assays for responsiveness to E1A. We found that a sequence capable of binding E4F could confer E1A inducibility. In contrast, a sequence that could bind ATF but not E4F did not confer E1A inducibility. We also found that E4F formed a stable complex with the E4 promoter, whereas the ATF DNA complex was unstable and rapidly dissociated. We conclude that the DNA-binding specificity of E4F as well as the alterations in DNA-binding activity of E4F closely correlates with E1A stimulation of the E4 promoter.